Effect of forest cover change on the prevalence of acute respiratory tract infections, diarrhoea, and fever among children under five: Using an ecosystem approach to child health - Amit Timilsina; Binaya Chalise; Kedir Y. Ahmed; Subash Thapa (PLoS ONE, 2025)
Introduction An ecosystem approach to child health emphasizes the interconnectedness of environmental, social, and biological factors in shaping children’s health and well-being. However, it is not known whether changes in forest cover have an effect on common childhood illnesses. This study investigated the associations between forest cover and acute respiratory infections (ARI), diarrhoea, and fever among children under five in Nepal. Method This was a cross-sectional study based on the analysis of the Nepal Demographic and Health Surveys (NDHS) datasets of 2011 (N = 5054) and 2016 (N = 4861). Forest cover data for the years 2011 and 2016 were extracted from high-resolution raster images from NASA Earthdata (30m resolution). We employed a logit model on the geo-linked NDHS datasets to compute the marginal effect of forest cover on ARI, diarrhoea, and fever. Results From 2011 to 2016, the prevalence of fever increased from 18% to 20%, while the prevalence of diarrhoea decreased from 14% to 7%, and ARI prevalence decreased from 5% to 3%. The mean tree cover percentage also decreased from 21% in 2011 to 19% in 2016. Forest cover was significantly associated with reduced likelihood of diarrhoea symptoms among children in both 2011 and 2016. Change in forest cover between 2011 and 2016 was significantly associated with a reduced probability of diarrhoea by 3.39% (Δy/Δx: −0.0339, 95% CI: −0.0141, −0.0535; p-value: 0.001), after adjusting for all other variables. No significant associations were found between forest cover change and changes in ARI and fever prevalence among children under five. Conclusion The present results should be interpreted cautiously, as they may not accurately reflect individual-level dynamics regarding the effect of forest cover on child health outcomes. The effect of forest cover in reducing childhood diarrhoea underscores the need for comprehensive child health programs that also incorporate environmental components.